2021
DOI: 10.7717/peerj.11407
|View full text |Cite
|
Sign up to set email alerts
|

Media exposure predicts acute stress and probable acute stress disorder during the early COVID-19 outbreak in China

Abstract: Background The COVID-19 has led to unprecedented psychological stress on the general public. However, the associations between media exposure to COVID-19 and acute stress responses have not been explored during the early COVID-19 outbreak in China. Methods An online survey was conducted to investigate the relationships between media exposure to COVID-19 and acute stress responses, and to recognize associated predictors of acute stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…We also found that the subjects with a history of psychosis at T1 might experience more symptoms of stress, and those with a history of psychosis at T4 showed more symptoms not only of stress but also of anxiety and depression. Luo et al also found that a history of mental illness was a risk factor for acute stress responses ( 54 ), and the outbreak of this pandemic was undoubtedly a crisis for those with a history of mental illness, which could affect their access to medical treatment and worsen their mental symptoms ( 5 ). Many of these individuals developed psychosis 1.5 years after the initial outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the subjects with a history of psychosis at T1 might experience more symptoms of stress, and those with a history of psychosis at T4 showed more symptoms not only of stress but also of anxiety and depression. Luo et al also found that a history of mental illness was a risk factor for acute stress responses ( 54 ), and the outbreak of this pandemic was undoubtedly a crisis for those with a history of mental illness, which could affect their access to medical treatment and worsen their mental symptoms ( 5 ). Many of these individuals developed psychosis 1.5 years after the initial outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China examined the association between media exposure about the COVID-19 pandemic and the stress response, and the study investigators found that prolonged exposure to the media was not only associated with higher levels of stress but also with acute stress disorder. This led to the recommendations that governments should be more conscious of the negative impacts that such exposure has on their citizens and should develop suitable mediation strategies that do not compromise citizen well-being but rather promote it in times of crisis [115].…”
Section: Minimizing Media Exposurementioning
confidence: 99%
“…In one study, an estimated one in five participants suffered from depressive symptoms and sleep disorders [3]. In addition, acute stress disorder (ASD) and post-traumatic stress disorder (PTSD) may be predicted by media exposure during the pandemic [4], as the Internet has become the primary source of information related to COVID-19 [5]. This created an enormous challenge for the existing mental health-care system in China.…”
Section: Introductionmentioning
confidence: 99%